Analisis Strategi Manajemen Operasional Mie Gacoan Mojokerto Dalam Perspektif Studi Kelayakan Bisnis - Dian Andamari Yekti; Abdur Rohman (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2024)
Indonesia is a popular country for its culinary variety. There are many different kinds of special food from different regions, every city has a special food, so many entrepreneurs who set up a culinary business especially the one that is in demand is meat-based meals. One of the biggest dining houses with a special taste of spicy meat is Mie Gacoan, a famous brand, with its own branches every city in the corner of the country of Indonesia.It's not every day that there are customers, there's always a lot of people coming. The aim of this study is to analyze operational management strategies that contribute to the success of Mie Gacoan's catering business. Using a qualitative research method that includes some library or literature studies, and using observations, the study identifies important factors that affect the operational performance and business success of the catering. The results of this research conclude that the operational management in the business success in Mie Gacoan Mojokekrto is very well structured from starting to choose a strategic environment, where choosing a lot of UMKM locations, designing the correct setting and price cuts so that many people are interested to hide it, because at cheap prices only we can enjoy a variety of menus. Then the quality of service is also very important from hospitality to hygiene. Have a strategic plan so as to provide new insights or innovations for entrepreneurs and practitioners in optimizing operational management strategies to sustainable business success in the long term.